Abordagem metabolômica e quimiométrica para avaliação dos componentes voláteis e não voláteis da Pitaya [Hylocereus polyrhizus (WEBBER) Britton & Rose] - Santos, Glauber Batista Moreira (2019)
The red pitaya (Hylocereus polyrhizus) also known as dragon fruit has its origin reported in the American continent and has attracted attention due to its coloration and benefits already studied. The effects of processing on the chemical, physicochemical, enzymatic, metabolomic and chemometric composition of Hylocereus polyrhizus were studied in this research. The following napitaya treatments were evaluated: Treatment A (without addition of ascorbic acid in the pulp), Treatment B (processing of whole fruits and addition of ascorbic acid in the pulp) and Treatment C (processing of whole fruits and without addition of ascorbic acid). In the studies of the analyzes involving enzymatic activities (polyphenoloxidase and peroxidase), chemical and physico-chemical characterization, the multivariate data analysis models were used, such as the main compound analysis (PCA), partial least squares (PLS- DA), Orthogonal Partial Least Squares discriminant analysis (OPLS-DA), projection importance variables (VIP) and heat maps (HEATMAP) to better understand and determine the correlation between chemical profile and treatments. In general, the data presented low protein content, low lipid content, being detected only in the seeds, with a higher carbohydrate presence in all fractions of the processes. Linoleic, oleic and palmitic acids were the most present in the seeds in both processes. Treatment B showed low polyphenoloxidase and peroxidase activity, with no significant chemical and physicochemical changes in most of the evaluated parameters, and a process with high yields than was compared with treatment A and treatment C. For the metabolomic analysis, chromatrography gas chromatography coupled to mass spectrometry (GC-MS) and ultra-high performance liquid chromatography coupled to mass spectrometry (UPLC-QTOF-MSE) were effective methods for the simultaneous determination of 80 and 35 metabolites, respectively volatile and non-volatile of the pitaya. All the chemometric analysis efficiently distinguished the applied treatments, and shows that treatment B presents a significant chemical profile due to the preservation or formation of new compounds.